2019
DOI: 10.35409/ijbmer.2019.2403
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Internal Controls on Financial Distress of Sasra Regulated Saccos

Abstract: Financial distress in SACCOs can be attributed to internal controls instituted by the board by the board of directors. While SACCOs are deemed to be stable and well governed by a board of directors who are accountable to SASRA for all internal controls of a firm, at times the controls put in place have not detected and or prevented fraudulent activities from taking place hence causing financial distress in SACCOs. This study was designed to evaluate internal controls instituted by the SACCOs and the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…The study showed that for every unit increase in internal controls, the performance of Imarisha SACCO increased by 0.045 units. Similar results have also been reported by Munene (2020). The regression model was structured in the following manner: Y = 1.214+ 0.469X1 +0.022X2 + 0.404X3 + 0.045X4, The constant value of 1.214 implies that at zero, board competence, legislation, roles and responsibilities and internal controls, performance is at 1.214 units.…”
Section: Research Findingssupporting
confidence: 74%
See 1 more Smart Citation
“…The study showed that for every unit increase in internal controls, the performance of Imarisha SACCO increased by 0.045 units. Similar results have also been reported by Munene (2020). The regression model was structured in the following manner: Y = 1.214+ 0.469X1 +0.022X2 + 0.404X3 + 0.045X4, The constant value of 1.214 implies that at zero, board competence, legislation, roles and responsibilities and internal controls, performance is at 1.214 units.…”
Section: Research Findingssupporting
confidence: 74%
“…Internal controls are accounting as well as auditing processes that organizations use to enhance service delivery (Alemu, 2020). The reason as to why organizations adopt internal control is that it helps the organizations to comply with laws as well as regulations as well as it aids in fraud prevention (Munene, 2020). The indicators of internal controls adopted in this study were oversight committees, internal and external audits as well as systems and processes.…”
Section: Journalmentioning
confidence: 99%